New Finds of Metal Tools of the Late Bronze Age in the Upper Tobol Region - Usmanova Emma R.; Merts Ilya V.; Merts Viktor K.; Yerzhanova Albina E.; Fomin Vitaliy N. (Поволжская археология)
The article presents an analysis of two accidental finds in the area of the villages of Novoilyinovka and Alchanovka (Kostanay oblast, Kazakhstan). The “Alchanovka” sickle belongs to the products of the Sosnovo-Mazino type, but differs by its zigzag ornament. The high iron content indicates the use of copper-pyrite ores as the raw material dating the sickle to the 14th–13th centuries BC and associate it with the Sargary-Alekseyevka culture. The “Novoilyinovka” celt is decorated on both sides by hanging triangles with ends in the form of “pearls”. By its morphological features, it is close to the products of the Maklasheyevka culture and Novoaleksandrovo groups of metal artifacts of the Late Bronze Age of Eastern Europe. Based on the chemical composition of the metal, it belongs to the Maklasheyevka culture of the Volga-Kama region, and possibly dates back to the 13th–12th centuries BC. Most likely, the “Novoilyinovka” celt is an import from the Volga-Kama region. The “Alchanovo” sickle and the “Novoilyinovka” celt reflect two stages within the period between the end of the Late Bronze Age-3 phase and the beginning of the Late Bronze Age-4 phase of the development of the West Asian (Eurasian) metallurgical province of Western Siberia.